2017
DOI: 10.1016/j.jalz.2017.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic analyses of familial and sporadic frontotemporal dementia patients in Southern Italy

Abstract: Introduction: We investigated the clinical differences between familial and sporadic frontotemporal dementia (FTD), screening for mutations in known FTD genes. Methods: We diagnosed 22 affected individuals belonging to 8 families and 43 sporadic cases with FTD in Apulia, Southern Italy in two years. Mutations in common causative FTD genes (GRN, MAPT, VCP and TARDBP) and C9ORF72 expansions were screened. Results: Behavioural variant of FTD was the most common clinical subtype (50% and 69% in familial and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 51 publications
(57 reference statements)
2
21
0
1
Order By: Relevance
“…We found out that subjective memory problems among bvFTD patients are notably common (84.0%), even though the prevalence was still significantly higher in AD patients (98.8%). In line with our finding, increasing evidence suggests that episodic memory can be markedly impaired even in the early stages of bvFTD [16][17][18][19][20][21]. Notably, it is important to differentiate subjective and objective memory disturbances, as they may in fact represent opposite phenomena.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found out that subjective memory problems among bvFTD patients are notably common (84.0%), even though the prevalence was still significantly higher in AD patients (98.8%). In line with our finding, increasing evidence suggests that episodic memory can be markedly impaired even in the early stages of bvFTD [16][17][18][19][20][21]. Notably, it is important to differentiate subjective and objective memory disturbances, as they may in fact represent opposite phenomena.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, relative sparing of memory performance is considered one of the main features of earlystage bvFTD, whereas episodic memory impairment and visuospatial problems are often early symptoms in patients with AD [2,12,13]. However, some studies have indicated that the phenotypes of both diseases may overlap clinically, and a significant proportion of bvFTD patients present with amnesia at the prodromal stages [14][15][16][17][18][19][20][21]. Furthermore, previous studies, including our own, have shown that patients with bvFTD may also manifest with early neuropsychiatric symptoms, such as depression and psychosis [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Our cohort of C9orf72 patients presents a high variability in age at onset, duration of the disease, familial forms, and number of affected family members, in accordance with the genetic epidemiology of Italian patients with FTD …”
Section: Discussionsupporting
confidence: 80%
“…Our cohort of C9orf72 patients presents a high variability in age at onset, duration of the disease, familial forms, and number of affected family members, in accordance with the genetic epidemiology of Italian patients with FTD. [31][32][33][34][35][36] These features reflect the incomplete and age-related penetrance of the mutation, that determines the high phenotypic heterogeneity characteristic of this pathology. As expected, there are no statistically significant differences in incidence among males and females and in the distribution of APOE e4 allele.…”
Section: Discussionmentioning
confidence: 99%
“…These include the inadequacy of current treatments to alleviate the symptoms of the disease. Also, the difficulty in developing novel interventions to detect [1–57], delay [58–69], or halt disease progression continues to be an important hurdle. The well‐recognized public health and economic imperative [70–83] posed by the disease continues to be an important motivator to communicate new knowledge across multiple disciplines that will help increase the likelihood of unlocking the complexity of neurodegeneration [84–90] associated with many dementing illnesses.…”
mentioning
confidence: 99%